Keterlibatan Siswa dalam Pembelajaran Bahasa Inggris - Nur Hasanah; Maria Ulfa; Eva Oktaviana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the supporting factors and challenges that influence student engagement in English learning among first graders at SDN 01 Kalisari. The research focuses on how teacher strategies, classroom interactions, and students’ emotional conditions contribute to their involvement in the learning process. A descriptive qualitative method was applied, using non-participant observation with multiple observers, supported by interviews with the subject teacher. The findings of this study indicate that students’ level of engagement varied across different indicators. Teacher–student interaction and activity variation received the highest scores, with 83.3% categorized as very good, whereas the teacher’s activeness in moving around the classroom obtained the lowest score, at 33.3% (low category). Several factors were identified as supporting engagement, including active teacher–student interaction, the use of diverse instructional media, the implementation of kinesthetic activities, the provision of verbal praise, as well as the incorporation of ice breaking activities, games, and songs that enhanced students’ enthusiasm. On the other hand, the main challenges observed were uneven learning motivation among students, limited instructional time in large classes, and the insufficient habituation of using English outside the classroom.. These findings highlight that young learners’ engagement in foreign language learning is shaped by a combination of pedagogical, emotional, and environmental factors. The study implies that developing creative and humanistic teaching strategies, as well as expanding opportunities for English use both inside and outside the classroom, is essential for sustaining student engagement